PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, PERCEIVED ENJOYMENT, PERCEIVED RISK, DAN E-WOM TERHADAP PURCHASE INTENTION PADA INSTAGRAM COMMERCE - Thereza May; Dewi Mustikasari Immanuel (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
Abstract: This study aims to know the effect of Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, Perceived Risk, dan E-WOM on the Purchase Intention of Instagram Commerce. Multiple Linear Regression analysis of SPSS been used in this study, the population in this study are people who active in social media Instagram. Samples were taken using the purposive sampling method with criteria men and women who are in Indonesia aged 18-34 years old who have intended to buy a product on social media Instagram using Instagram Commerce feature within the last one year with total 385 samples. Data collection in this study was carried out by distributing questionnaires to respondents. The results of this study indicate that Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, and E-WOM have a positive and significant effect on purchase intention of Instagram Commerce. Perceived Risk has positive and significant effects on the purchase intention of Instagram Commerce. Keywords: E-WOM, Instagram Commerce, Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, Perceived Risk, Purchase Intention.